The Effectiveness of Problem Based Learning Model with SMT Media Reviewed from Learning Results and Careful Attitude to Students' Materials of Multipling Class III - Desi Ambar Sari; Rusnilawati Rusnilawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Mathematics as one of the subjects in school is considered to play an important role in education. Based on the Minister of National Education Regulation No. 20 of 2003 concerning the National Education System (National Education System) article 37 it is emphasized that, "Mathematics is one of the compulsory subjects for students at the basic education level". The purpose of this study is to describe the effectiveness of the application of the Problem Based Learning model with TAKALINTAR media, which is better than the Direct Instruction model with multiplication media in terms of student learning outcomes in grade III multiplication material. The results of the study stated that the PBL learning variable had a direct and significant effect on Learning Outcomes and Attitudes. This can be seen from the results of the partial test (T test) which shows that the tcount value is greater than the ttable value, namely (3.802 < 1.617) and the significance value is 0.000 > 0.05. This means that the H1 hypothesis is accepted, namely that there is an influence of the free shipping promotion variable on the Learning Outcomes and Attitudes variable in grade 3 A and B students of SD N Nangsi.